Diagnostic Challenges and Treatment of Concurrent Toxoplasmosis and Disseminated Cryptococcus in an Immunocompromised Patient - Jeffrey Valencia Uribe; Ann-Katrin Valencia; Brian Nudelman; Nicole Nudelman; Dante P. Melendez Lecca (Case Reports in Infectious Diseases)
Conclusion: Diagnosing concurrent cryptococcal and toxoplasma infections is challenging due to overlapping clinical symptoms and variability in test sensitivities. This case underscores the need for a comprehensive diagnostic approach and the critical role of brain biopsy when other diagnostic methods, such as Karius testing and CSF PCR, are inconclusive. Prompt empirical treatment based on clinical suspicion, with subsequent treatment adjustments guided by clinical response and follow-up assessments, is essential for effective management.